A development of electromagnetic retarder controller to stabilise vehicle speed by using PWM technique. (1st January 2014) - Ergün, Riza Emre; Uçar, Mehmet; Ertunç, Hüseyin Metin; Cengiz, Abdulkadir
Deceleration of heavy vehicles on long downhill runs is an important problem. Because of heavy loads, they have a huge amount of kinetic energy to be absorbed. Electromagnetic retarders are widely used on heavy vehicles owing to low operating and maintenance costs. In this study, a braking control system that can be easily applied to existing electromagnetic retarders of vehicles was designed and tested experimentally. The goal of the proposed system is deceleration of the vehicle and stabilisation of the speed at a desired value by using an electromagnetic retarder. To achieve this goal, a closed-loop pulse width modulation (PWM) braking controller was designed. For the experiments, an experimental set-up consisting of an electromagnetic retarder and an engine was built. As a result of experiments, the engine running at a constant speed was decelerated in a controlled manner with a 4% steady-state error according to setpoint values.